P-016 Successful Flow Diversion of Cerebral Aneurysms in Plavix Hyporesponders (PRU ≥ 200): An Argument for Antiplatelet Monotherapy?. (29th July 2016) - Colby, G; Lin, L; Lubelski, D; Bender, M; Xu, R; Jiang, B; Huang, J; Tamargo, R; Coon, A
Abstract : Introduction: Endovascular aneurysm treatment by flow diversion has classically relied on dual anti-platelet therapy with Aspirin and Plavix to reduce thrombotic complications. The heterogenous Plavix response of patients has made P2Y12 testing increasingly popular. Plavix hyporesponders (defined as PRU ≥ 200) are often re-dosed with Plavix or switched to alternate anti-platelet regimens. However, little clinical validation exists for these practices, and they might actually increase risks of hemorrhagic complications. We sought to evaluate periprocedural outcomes following flow diversion in patients maintained on standard Aspirin and Plavix regimens with PRU ≥ 200. Methods: A single-center prospectively collected aneurysm database was reviewed for adult patients on standard dual antiplatelet regimens (Aspirin 325 mg + Plavix 75 mg daily) who underwent endovascular embolization of ICA and proximal ACA/Acom aneurysms with the Pipeline Embolization Device (PED). Patients with pre-embolization P2Y12 testing and PRU level ≥200 were included. Results: 49 patients (mean age 56, 74% women) met inclusion criteria. Forty-seven (96%) patients had a single aneurysm treated, and 2 (4%) had 2 aneurysms treated; 84% of aneurysms were on the ICA and 16% on the ACA (Acom and A1-2). Aneurysm size ranged from 2–28 mm. PED length ranged from 10–35 mm. Pre-procedure PRU levels ranged from 200 to 361. RePro was administered in 5/49 (10%) cases, with platelet plug visualized in 4/49 cases (8%). Four patients (8%) had transient neurological deficits (resolved completely during hospital stay), with only 1 of these requiring ReoPro during the procedure. No patients had major or minor permanent strokes, and no patients had hemorrhagic complications. Conclusions: Hyporesponse to Plavix (PRU ≥ 200) is not a contraindication to aneurysm treatment with the PED in patients on a standard dual antiplatelet regimen of Aspirin 325 mg and Plavix 75 mg daily. These data suggest a diminutive role of Plavix in preventing thrombotic complications during these procedures. Disclosures: G. Colby: 1; C; Stryker, Medtronic. 2; C; Microvention. L. Lin: 1; C; Stryker. D. Lubelski: None. M. Bender: None. R. Xu: None. B. Jiang: None. J. Huang: None. R. Tamargo: None. A. Coon: 1; C; Sequent. 2; C; Stryker, Medtronic, Microvention, Sequent.